2016
DOI: 10.1038/modpathol.2016.50
|View full text |Cite
|
Sign up to set email alerts
|

Post-ablation lymphocytic esophagitis in Barrett esophagus with high grade dysplasia or intramucosal carcinoma

Abstract: In patients who have undergone ablation therapy for treatment of Barrett's esophagus with dysplasia, histologic features of eosinophilic esophagitis, but not lymphocytic esophagitis, have been described. We evaluated for histologic evidence of eosinophilic esophagitis and lymphocytic esophagitis and correlated with endoscopic findings in this population. A single-institution Barrett's esophagus registry was searched for patients who had received radiofrequency ablation, cryotherapy, or both for treatment of Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
1
10
2
Order By: Relevance
“…To the best of our knowledge, only three case reports in the English literature described cases of LE outside the United States, including Japan[ 19 ], Portugal[ 20 ] and Australia[ 21 ]. In contrast to the findings of Rubio et al[ 1 ], it is becoming evident that LE seems to affect older women to a larger extent, in their sixth decade[ 12 , 14 , 17 , 18 ], in contrast to eosinophilic esophagitis (EoE) seen in younger men. Smoking was also found to be associated with LE in multiple retrospective studies[ 14 , 17 ].…”
Section: Clinical Features Of Lecontrasting
confidence: 59%
See 1 more Smart Citation
“…To the best of our knowledge, only three case reports in the English literature described cases of LE outside the United States, including Japan[ 19 ], Portugal[ 20 ] and Australia[ 21 ]. In contrast to the findings of Rubio et al[ 1 ], it is becoming evident that LE seems to affect older women to a larger extent, in their sixth decade[ 12 , 14 , 17 , 18 ], in contrast to eosinophilic esophagitis (EoE) seen in younger men. Smoking was also found to be associated with LE in multiple retrospective studies[ 14 , 17 ].…”
Section: Clinical Features Of Lecontrasting
confidence: 59%
“…A better immunophenotypic characterization of LE is hence needed for a superior definition. Another aspect of deficiency in the definition of LE is reflected in the various studies performed with different cut-offs used to demarcate an increased IEL count, ranging between ≥ 10 IEL/HPF[ 14 ] and ≥ 50 IEL/HPF[ 15 , 16 ] with a cut off of ≥ 20 IEL/HPF being commonly used[ 17 , 18 ]. Moreover, the acceptable number of a " few granulocytes " needs to be better defined, as granulocytic inflammation is typically seen in GERD.…”
Section: Histopathologymentioning
confidence: 99%
“…Kissiedu et al . reported a higher rate of intraepithelial lymphocytosis in postablation biopsies compared with preintervention samples among 102 patients with Barrett esophagus and dysplasia …”
Section: Clinical Significance Of Lymphocytic Esophagitis In the Absementioning
confidence: 98%
“…15 Kissiedu et al reported a higher rate of intraepithelial lymphocytosis in postablation biopsies compared with preintervention samples among 102 patients with Barrett esophagus and dysplasia. 16 Once the abovementioned disorders are excluded, lymphocytic esophagitis may be associated with several important conditions. It is clearly a manifestation of Crohn's disease among pediatric patients, but there is no established association between Crohn's disease or celiac disease and lymphocytic esophagitis in adult patients.…”
Section: Clinical Significance Of Lymphocytic Esophagitis In the Absementioning
confidence: 99%
“…(2, 3) Previous studies report associations of LE with achalasia, Crohn’s disease in children, post-ablation status in Barrett esophagus, common variable immunodeficiency, lichen planus and some other dermatological disorders. (3, 611) However, in the majority of adult patients with LE clinical correlates have not been established. (24) We have recently proposed a link between LE and esophageal dismotility patterns.…”
Section: Introductionmentioning
confidence: 99%